An Architect as an Anthropological Issue - Rappaport, Alexander (project baikal, 2018)
An architect is an anthropological issue, because we don’t know what architecture is and whether a human being is able to create it. Inferiority of existence of architecture as a profession always leads architects, on the one hand, to delusion of grandeur and infallibility, and, on the other hand, to despair and self-conceit. This part of the matter is never covered in criticism, polemics or memoirs. A new, not yet born branch of architectural studies, the professional anthropology of the architect, can reveal the hidden sides of the profession and help architects in their self-determination.
Keywords: architecture; profession; architect; anthropology of the architect as a new branch of architectural studies